Does a Fundamentalist Mindset Predict a State or Trait Anxiety? The Covariate Role of Dogmatism - Carlucci, Leonardo (Journal of religion and health, 2021)
Recent neuropsychological studies reported that fundamentalism beliefs and its cognitive mindset provoke sense of coherency and protection against the ambiguity as well as a rapid doubt resolution and thus offer relief from distress and uncertainty. In this study, we examined whether the need for closure dimensions predicted religious fundamentalism. Further, we tested if pronounced religious beliefs (also controlled for dogmatism) would be associated with a state or trait anxiety, in a sample of 388 Roman Catholics (females = 53.9%). Path analysis (SEM), with observed variables, was used to determine the pathways by which religious fundamentalism, need for closure dimensions, and dogmatism interacted to influence anxiety. The results revealed that religious fundamentalism was predicted by intolerance to ambiguity, preference for order, and closed-mindedness; in turn, high fundamentalism scores predicted state anxiety exclusively. Additionally, when controlling for dogmatism, the fundamentalism-anxiety path became nonsignificant. Although it seemed that fundamentalism beliefs “per se” have played no direct anxiolytic effect, they partially perform a function of avoiding chaos and disorder in order to maintain cognitive integrity.